The art of the landscape - Milani, Raffaele (McGill-Queen's University Press, 2009)
Aesthetics deals with art, a human construction, but what one experiences when placed before nature is also an aesthetic feeling - the countryside is a place of reflection like no other. In The Art of the Landscape, Raffaele Milani interprets natural landscapes as an aesthetic category.